Growth and linear optical properties of CuCl nanocrystals - Mahtout, S.; Belkhir, M.A.; Samah, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Linear optical properties of CuCl nanocrystals in a NaCl matrix have been studied using optical absorption, cathodoluminescence and X-ray diffraction measurements. Our measurements showed that CuCl nanocrystals were really formed. Their average size was estimated to be 2.2 nm. Consistently with confinement effect resulting from the low size of the nanocrystals, a blue shift of excitonic levels is observed by comparison to the bulk crystal. Our analysis showed that the effect of thermal annealing depends on the temperature, the annealing time and the nature of cooling.